mTOR Inhibitors as Radiosensitizers in Neuroendocrine Neoplasms - Exner, Samantha; Arrey, Gerard; Prasad, Vikas; Grötzinger, Carsten (Frontiers in Oncology, 2021)
Peptide receptor radioligand therapy (PRRT) has evolved as an important second-line treatment option in the management of inoperable and metastatic neuroendocrine neoplasms (NEN). Though high radiation doses can be delivered to the tumors, complete remission is still rare. Radiosensitization prior to PRRT is therefore considered to be a promising strategy to improve the treatment effect. In this study, effect and mechanism of mTOR inhibitors were investigated in a comprehensive panel of five NEN cell lines (BON, QGP-1, LCC-18, H727, UMC-11), employing assays for cellular proliferation, clonogenic survival, cell cycle modification and signaling. mTOR inhibition lead to growth arrest with a biphasic concentration-response pattern: a partial response at approximately 1 nM and full response at micromolar concentrations (8-48 µM). All cell lines demonstrated elevated p70S6K phosphorylation yet also increased phosphorylation of counterregulatory Akt. The pulmonary NEN cell line UMC-11 showed the lowest induction of phospho-Akt and strongest growth arrest by mTOR inhibitors. Radiation sensitivity of the cells (50% reduction versus control) was found to range between 4 and 8 Gy. Further, mTOR inhibition was employed together with irradiation to evaluate radiosensitizing effects of this combination treatment. mTOR inhibition was found to radiosensitize all five NEN cells in an additive manner with a moderate overall effect. The radiation-induced G2/M arrest was diminished under combination treatment, leading to an increased G1 arrest. Further investigation involving a suitable animal model as well as radioligand application such as 177Lu-DOTATATE or 177Lu-DOTATOC will have to demonstrate the full potential of this strategy for radiosensitization in NEN.